Kaidah Bahasa Indonesia Dalam Penulisan Karya Ilmiah Pada Guru SMA Purnama 2 Jakarta-Selatan - Rahmawati Rahmawati (Peneliti.net, 2021)
Indonesian language rules are one of the important guidelines in writing scientific papers. Writing scientific papers will never be separated from the rules of the Indonesian language because scientific works are always related to language. Indonesian language rules are not only about spelling, but also about sentences, paragraphs, punctuation, and so on. In writing scientific papers, language is a system used as a written communication tool. This system is the medium in conveying the intent and purpose of writing scientific papers. In society, humans need a means to convey information, thoughts, intentions or goals, and so on. Writing scientific papers is an academic necessity. By writing, a person can communicate ideas and learning problems that they do every day. A good writing is communicative writing, meaning that the message conveyed is understood by the reader as the author intended. Communicative writing is conveyed through languages ​​that are systematically arranged, easy to understand, not long-winded, and not ambiguous. Indonesian language rules are very important in scientific writing, the application and use of appropriate and correct Indonesian language rules in scientific works will make it easier to convey the intent and purpose of writing scientific papers.